A simple and efficient method for the synthesis of 5, 6-dihydropyrazin-2(1H)-one O-(tert-butyl)oximes, quinoxalin-2(1H)-one O-(tert-butyl)oximes and its derivatives. Issue 46 (14th November 2018) - Aoyama, Tadashi; Tashiro, Kenshiro; Hayakawa, Mamiko; Shimada, Shigeru; Ouchi, Akihiko
Graphical abstract: Highlights: A simple and efficient method for the synthesis of 5, 6-dihydropyrazin-2-ones and quinoxalin-2-ones. Applications of N-tert -butoxy acyl imidoyl bromide to the synthesis of 5, 6-dihydropyrazin-2-ones and quinoxalin-2-ones. All synthesized products have Z-stereochemistry in regard to the CN double bond. Abstract: A simple and efficient method was developed for the synthesis of 5, 6-dihydropyrazin-2(1 H )-one O -( tert -butyl)oximes, quinoxalin-2(1 H )-one O -( tert -butyl)oximes and its derivatives from N - tert -butoxy acyl imidoyl bromide and diamines. Twenty three novel compounds were readily synthesized using this procedure in excellent yields. The products possessed Z -stereochemistry with regard to the CN double bond. In these reactions, the amino group first attacked an imidoyl carbon of the N - tert -butoxy acyl imidoyl bromide in order to obtain the Z -intermediate; then another amino group attacked the carbonyl carbon of the intermediate. The rate of intramolecular cyclization of the intermediate was dependent on the position of the diamino groups.